First description of egg masses, oviposition and copulation of a neglected apple snail endemic to the iguazú and Alto Paraná Rivers - Gurovich, Fernanda Mariel (2017)
The Ampullariidae have attracted persistent scientific interest, although this has been mostly concentrated on a few invasive species. Pomacea americanista (Von Ihering, 1919) new combination is a neglected species as there has been no published information about its anatomy and natural history since its description in 1919. Our aim was to describe its egg masses, oviposition and copulation to compare them with those of other Ampullariidae. We made observations on egg masses in the Iguazú River and tributaries and on snails reared in the laboratory. Pomacea americanista exhibited the same reproductive mode as other Pomacea species: aerial egg masses composed of hundreds (mean 186.12) of eggs with calcareous shells (mean 3.1 mm in diameter) that are deposited on emergent substrates, mostly rocks. The egg masses were a characteristic pale pink that distinguishes them from those of other species of Pomacea. Embryonic development took nearly 17 days at 26 °C. Hatchlings had a smooth shell with 1⅛ whorls (mean 2.6 mm in diameter) and began to breathe air and feed within a few hours. Copulation was subaquatic and long lasting (mean 16.13 h) and both sexes were highly promiscuous. The evidence gathered supports the hypothesis that P. americanista belongs to the genus Pomacea.